The Pathology of Morphine-Inhibited Nerve Repair and Morphine-Induced Nerve Damage Is Mediated via Endoplasmic Reticulum Stress - Liu, Jie; Yi, Shanyong; Shi, Weibo; Zhang, Guozhong; Wang, Songjun; Qi, Qian; Cong, Bin; Li, Yingmin (Frontiers in Neuroscience, 2021)
Objective: The present study aimed to observe the pathological damage of cerebral cortex in rats with acute morphine exposure and different durations of morphine dependence, explore whether endoplasmic reticulum stress (ERS) is involved in the damage process and the effect of morphine exposure on proliferation and differentiation of newborn neurons. Methods: Rat models with acute morphine exposure and different durations of morphine dependence were established. The pathological changes of cortical neurons were observed by HE staining and thionine staining. Expression of Nurr1 and ERS- related proteins GRP78, p-eIF2α, ATF6, CHOP in the cortical neurons were observed by immunohistochemical staining. Immunofluorescence double labeling were used to observe the expression of Ki67. Results: HE staining and thionine staining revealed that acute morphine exposure resulted in pyknosis changes in cortical neurons, and with prolonged morphine exposure, the number of pyknotic neurons increased significantly, Ki-67, Nurr1 protein expression significantly decreased, while the expression of ERS-related proteins GRP78, p-eIF2α, ATF6, CHOP showed obvious dynamic changes. Conclusion: Acute morphine exposure and different durations of morphine dependence caused varying degrees of pathological changes in cortex, and the dynamic changes of ERS-related proteins suggested that ERS may be associated with cortical injury; different durations of morphine dependence inhibited the proliferation, differentiation and migration of newborn neurons, which may affect the nerve repair process after injury.